Hubungan Pola Asuh Lingkungan Dan Penggunaan Gadget Terhadap Kejadian Kehamilan Diluar Nikah Di Wilayah Cisimeut - Wahyuni, Nur Ismi; Nining (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: According to the World Health Organization (WHO), more than 500 million teenagers aged 10-14 years in developing countries have had sex for the first time under the age of 15 years. Approximately 60% of pregnancies that occur in teenagers in developing countries are unwanted pregnancies and 15 million teenagers have given birth. Methods: This type of research is a correlation analytical method with a cross sectional design. The sample collection technique for the case samples carried out in this research was proportional random sampling technique. The sample used is 50 teenagers who will be divided into 2 groups, namely those who are pregnant out of wedlock and those who are not pregnant. The instrument that will be used in this research is a questionnaire Results: The relationship between environmental parenting patterns and the incidence of pregnancy outside of marriage was carried out using a statistical analysis test using the chi-square test, resulting in a p-value of 0.038 < (0.05), and the relationship between the use of gadgets and the incidence of pregnancy outside of marriage was obtained by statistical analysis using the chi tes. -square p-value 0.395 > (0.05) Conclusion: there is a significant relationship between environmental parenting patterns and the incidence of pregnancy outside of marriage, but there is no relationship between the use of gadgets and the incidence of pregnancy outside of marriage.